Immunochemical and ultrastructural study of multiple myeloma with a heavy chain protein in the serum. Issue 10 (October 1980) - Bartoloni, C; Flamini, G; Gentiloni, N; Russo, M A; Barone, C; Gambassi, G; Terranova, T
Abstract : A patient with multiple myeloma had antigenically related monoclonal Fc-gamma fragments and complete IgG-kappa molecules in the serum. The urine contained only Fc-gamma fragments in the absence of Bence-Jones protein. The two distinct M-components in the serum showed electrophoretic identity but could be separated by chromatography. The simultaneous presence of complete monoclonal IgG molecules and Fc-gamma fragments, though difficult to detect, could be a frequent occurrence in multiple myeloma, and it could be defined as 'double paraproteinaemia'. A detailed ultrastructural study was performed in this case and showed fibril bundles being released from the malignant plasma cells; such fibrils could be the supramolecular organisation of the neosynthesised heavy chain fragments.